2007
DOI: 10.3748/wjg.v13.i11.1652
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of apoptotic effects induced selectively by ursodeoxycholic acid on human hepatoma cell lines

Abstract: AIM:To investigate the effects of ursodeoxycholic acid (UDCA) on apoptosis and proliferation of hepatoma cell lines. METHODS:Human hepatoma cell lines HepG2 and BEL 7402 were cultured in medium supplemented with different concentrations of UDCA, normal human hepatic line L-02 was used as control. Cell proliferation, apoptosis and gene expression were detected using methyl thiazolyl tetrazolium (MTT) assay, flow cytometry, Western blot, DNA ladder assay, electron microscopy, and immunocytochemistry. RESULTS:Urs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
8

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
1
14
0
8
Order By: Relevance
“…Regarding the HepG2 cells, results are somewhat contradictory as UDCA may induce apoptosis, but it seems that this effect may depend on the UDCA concentration. Thus, concentrations higher than 100 lM resulted in increased apoptosis, while lower concen trations clearly decrease a TNF-alpha and LCA-induced apoptosis in these cells [37][38][39], data which are consistent with those observed in this study. Actually, 10 and 100 lM UDCA decreased apoptosis in HepG2 cells, particularly when it was induced by CAM.…”
Section: European Journal Of Clinical Investigation Vol 44 1209supporting
confidence: 91%
“…Regarding the HepG2 cells, results are somewhat contradictory as UDCA may induce apoptosis, but it seems that this effect may depend on the UDCA concentration. Thus, concentrations higher than 100 lM resulted in increased apoptosis, while lower concen trations clearly decrease a TNF-alpha and LCA-induced apoptosis in these cells [37][38][39], data which are consistent with those observed in this study. Actually, 10 and 100 lM UDCA decreased apoptosis in HepG2 cells, particularly when it was induced by CAM.…”
Section: European Journal Of Clinical Investigation Vol 44 1209supporting
confidence: 91%
“…24,29,41 The activity of UDCA to suppress cholestatic liver disease has been intensively studied by many investigators and is attributed to the compounds' cytoprotective roles that include the prevention of pro-apoptotic gene expression, collapse of the mitochondrial membrane potential, or death receptor-mediated cell death events. 31,33,[42][43][44] On the other hand, UDCA has been shown to exert tumor suppressing activity by pro-apoptotic mechanisms 32,33 and enhance CPT-11 induced-apoptosis in colon cancer cells and promote an apoptotic response of tumor cells to photosensitizers and Bcl-2/Bcl-X L antagonist HA14-1. 45,46 Pro-apoptotic activity of UDCA was also demonstrated in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Furthermore, recurrence of colorectal adenomas with highgrade dysplasia in a phase III trial was shown to be decreased after treatment with UDCA. 30 Although the tumor suppressive activity of UDCA is believed to be linked to the induction of apoptosis and cell cycle arrest, and the inhibition of oncogenic factors including Ras and COX-2, in human cancer cell lines, [31][32][33] these mechanisms are not yet fully understood. In this study, we examined the effects of UDCA on platinuminduced cell death and demonstrate a novel activity of UDCA in switching platinum drug-induced cell death mode from necrosis to apoptosis, suggesting a possible beneficial role of UDCA in platinum-based anti-cancer chemotherapy.…”
mentioning
confidence: 99%
“…However, the effect of UDcA on human Hcc cells has not yet been elucidated yet. It has recently been reported that UDcA selectively inhibited cellular proliferation and induced apoptosis in human hepatoma cell lines by blocking the cell cycle and regulating Bax/bcl-2 gene expression (30). In another experiment, the addition of UDcA into human Huh-7 and rat Fao Hcc cells induced apoptosis in a dose-dependent manner (31).…”
Section: Discussionmentioning
confidence: 97%